2016
DOI: 10.3892/etm.2016.3604
|View full text |Cite
|
Sign up to set email alerts
|

Acute transverse myelitis and subacute thyroiditis associated with dengue viral infection: A case report and literature review

Abstract: Abstract. Acute transverse myelitis is a rare manifestation of dengue infection. To the best of our knowledge, only 6 cases of acute transverse myelitis as a manifestation of dengue infection have been reported thus far. The present study described a case of acute transverse myelitis complicated with subacute thyroiditis 6 days after the onset of dengue viral infection. In addition, the available literature was searched to identify similar previous cases. Treatment with intravenous pulse methylprednisolone imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In Japan, the ratio of women to men was 6, 4 and 7 in 1970s, 1980s and 1996-2004, respectively [12][13][14]. The incidence of subacute thyroiditis in women varied widely by region and time, which may be explained by the association of development of subacute thyroiditis with various bacterial and viral infections [15][16][17][18][19][20][21]. Seasonal changes of the incidence of subacute thyroiditis support our hypothesis [7].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In Japan, the ratio of women to men was 6, 4 and 7 in 1970s, 1980s and 1996-2004, respectively [12][13][14]. The incidence of subacute thyroiditis in women varied widely by region and time, which may be explained by the association of development of subacute thyroiditis with various bacterial and viral infections [15][16][17][18][19][20][21]. Seasonal changes of the incidence of subacute thyroiditis support our hypothesis [7].…”
Section: Discussionsupporting
confidence: 71%
“…Further, a significant association between subacute thyroiditis and infection has been reported [15][16][17][18][19][20][21]. Steroid levels increase immediately after stress such as infection in response to the stimulation of corticotropin-releasing hormone secretion by various cytokines [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammatory reactions in the CSF are found in most patients. TM/LETM in dengue is rarely encountered, and no more than 12 case reports are available (Renganathan et al, 1996 ; Leao et al, 2002 ; Kunishige et al, 2004 ; Seet et al, 2006 ; Chanthamat and Sathirapanya, 2010 ; Verma et al, 2011a ; Larik et al, 2012 ; Singh et al, 2013 ; Weeratunga et al, 2014a ; Fong et al, 2016 ; Mo et al, 2016 ; Mota et al, 2017 ).…”
Section: Central Neurological System Complicationsmentioning
confidence: 99%
“…Fong et al reported that a previously healthy 12-year-old girl with parainfectious-dengue TM and concomitant spinal epidural haematoma had good clinical recovery without surgical intervention after 6 months (Fong et al, 2016 ). It was shown that post-infection autoimmune reactions and direct infection are associated with transverse myelitis (Solomon et al, 2000b ; Sindic et al, 2001 ; de Sousa et al, 2014 ; Mo et al, 2016 ).…”
Section: Central Neurological System Complicationsmentioning
confidence: 99%
“…A further 136 were excluded on the basis of title and abstract and 19 studies did not meet the eligibility criteria on full text screening ( Figure 1). The remaining 25 studies were eligible and full text was assessed for inclusion in the final review [7,9,10,[12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Most of the studies were from Asia (76%; 19/25) and the rest from South America (24%; 6/25).…”
Section: Resultsmentioning
confidence: 99%